1969
DOI: 10.1063/1.1657472
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Dislocations in Aluminum

Abstract: The velocities of individual dislocations of edge and mixed types in pure aluminum single crystals were determined as a function of applied-resolved shear stress and temperature. The dislocation velocities were determined from measurements of the displacements of individual dislocations produced by stress pulses of known duration. The Berg-Barrett x-ray technique was employed to observe the dislocations, and stress pulses of 15 to 108 !'sec duration were applied by propagating torsional waves along the axes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(35 citation statements)
references
References 17 publications
5
29
1
Order By: Relevance
“…Unfortunately, their support for this model was based upon the assumption that the mean dislocation velocity did not vary during deformation from yield to fracture. This is an oversimplification; Gorman et al 62 have shown that dislocation velocity is proportional to flow stress in aluminium and it is quite possible for the mean speed of dislocations to vary by as much as a factor of 100 during a test.…”
Section: Single Crystalsmentioning
confidence: 97%
“…Unfortunately, their support for this model was based upon the assumption that the mean dislocation velocity did not vary during deformation from yield to fracture. This is an oversimplification; Gorman et al 62 have shown that dislocation velocity is proportional to flow stress in aluminium and it is quite possible for the mean speed of dislocations to vary by as much as a factor of 100 during a test.…”
Section: Single Crystalsmentioning
confidence: 97%
“…For a Volterra dislocation in a linear elastic continuum, Frank [4] and Eshelby [5,6] found the elastic energy of a uniformly moving dislocation diverged at the transverse speed of sound, which suggested the existence of a limiting speed for dislocations. Early experimental studies of dislocation mobility also suggested a saturation of glide speeds as the speed of sound is approached [7][8][9][10]. Since then, continuum models of increasing complexity have been proposed to describe dislocation glide [11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…Greenman et al [24] showed experimentally that for Cu = m 0.7. For Al, Gorman et al [41] reported a linear dependence of v on at a low speed region. The measurement by Yasutake et al [25] for twinning partial dislocations in silicon suggests a distinct dependence of dislocation velocity on stress, which is better captured with = m 2.73.…”
Section: Resultsmentioning
confidence: 99%